2009
DOI: 10.1093/cvr/cvp252
|View full text |Cite
|
Sign up to set email alerts
|

The G protein coupled receptor kinase 2 plays an essential role in beta-adrenergic receptor-induced insulin resistance

Abstract: Our results suggest that GRK2 mediates adrenergic IRES and that inhibition of GRK2 activity leads to increased Ins sensitivity both in cells and in animal model of IRES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 33 publications
7
106
0
1
Order By: Relevance
“…GRKs have been proposed to be modulators of cellular functions in a phosphorylation-independent manner due to their ability to interact with a variety of signaling and trafficking proteins, such as actin (79), actinin (80), tubulin (37), G␣ (36), G␤␥ (187), clathrin (225), PI3K (164), GIT (190), caveolin (36, 88), lipids, etc. GRKs have been placed in the center of regulatory processes involving cell migration (179), metabolism (50,52,254), and apoptosis (43). Further investigation is needed to address these GRK-mediated intermolecular interactions and how they link to various cellular processes.…”
Section: E Regulation Of Grksmentioning
confidence: 99%
“…GRKs have been proposed to be modulators of cellular functions in a phosphorylation-independent manner due to their ability to interact with a variety of signaling and trafficking proteins, such as actin (79), actinin (80), tubulin (37), G␣ (36), G␤␥ (187), clathrin (225), PI3K (164), GIT (190), caveolin (36, 88), lipids, etc. GRKs have been placed in the center of regulatory processes involving cell migration (179), metabolism (50,52,254), and apoptosis (43). Further investigation is needed to address these GRK-mediated intermolecular interactions and how they link to various cellular processes.…”
Section: E Regulation Of Grksmentioning
confidence: 99%
“…However, recent evidence has shown that GRK2 can restrain signaling via direct interaction with downstream intracellular kinases, including Akt, extracellular signal-regulated kinase 1/2 (ERK1/2), phosphatidylinositol 3-kinase, and p38, leading to modulation of their activity (Liu et al, 2005;Jimenez-Sainz et al, 2006). Furthermore, GRK2 can also regulate signaling mediated by other membrane receptor families, such as tyrosine kinase receptors for insulin, insulin-like growth factor 1, platelet-derived growth factor, and epidermal growth factor (Kim et al, 2003;Cipolletta et al, 2009). Thus, it should be stressed that the cellular role of GRK2 is not limited to promoting b-arrestin binding to activated GPCRs.…”
Section: Introductionmentioning
confidence: 99%
“…59 Insulin administration increases GRK2 cellular levels within 15-30 minutes. 61 Insulin-like growth factor-1 induces GRK2 cellular accumulation by inhibiting mouse double minute 2 (Mdm2), which is responsible for kinase ubiquitination and degradation. 62 Chronic insulin treatments are characterized by increased GRK2 levels.…”
Section: Grk2 Functions and Involvement In Human Diseasesmentioning
confidence: 99%
“…In addition to peptides derived from the first intracellular loop of the hamster β 2 -AR, small peptides derived from GRK2/3 KD were tested in animal models of diabetes to investigate the treatments for type 2 diabetes 113. GRK2 inhibition can lead to the restoration of signaling pathways involved in glucose homeostasis control 59,61,63,114. Acylated glycine derivatives of short peptides, such as myristyl…”
mentioning
confidence: 99%